Regular Physical Activity, High Soy Dietary Intake and Premenstrual Syndrome (PMS) Symptoms in Young Adult Women: A Descriptive Study - Kusumawardani, Eva Flourentina; Adi, Annis Catur (Universitas Wijaya Kusuma Surabaya, 2019)
Premenstrual syndrome (PMS) in adolescents group is one of the most common disorder in woman at reproductive age. It substantially reduces quality of life for many women of reproductive age, with pharmaceutical treatments having limited efficacy and substantial side effects. A health lifestyle e.g. regular physical activity and high soy dietary intakes has been recommended as a method of reducing PMS symptoms. This study aims to describe the physical activity and high soy dietary intake and PMS symptoms in female students of Vocational High School 10 Surabaya. This study was designed to describe the activity level were recalled in 7x24 hour, soy dietary intake, and severity of PMS symptoms in female students that was administrated by structured questionnaires. The result showed that of all participants (n=59) were defined as having light physical activity level (88.1%), moderate level of soy dietary intake (17.22-28.38 portions per month), and mild degree of PMS symptoms (71.2%). Based on crosstabulation showed that respondences who had light physical activity experienced moderate PMS degree (8.6%), and who had high soy dietary intake experienced moderate PMS degree (8.5%). This recommendation is based on relatively little evidence, and the relationship between physical activity, soy dietary intake, and premenstrual syndrome symptoms remains unclear.